Understanding Disease–Drug Interactions in Cancer Patients: Implications for Dosing Within the Therapeutic Window. Issue 1 (19th May 2015) - Coutant, DE; Kulanthaivel, P; Turner, PK; Bell, RL; Baldwin, J; Wijayawardana, SR; Pitou, C; Hall, SD
<x xml:space="preserve">Abstract</x> The human inflammatory response can result in the alteration of drug clearance through effects on metabolizing enzymes or transporters. In this article we briefly review the theory of how cancer can lead to indirect changes in drug metabolism, review acute phase proteins and cytokines as markers of changes in cytochrome P450 (CYP) activity in cancer patients, and provide clinical case examples of how the inflammation in advanced cancer patients can lead to altered CYP‐mediated drug clearance.